Anomalous temperature dependence of the effective mass in p-type Bi2Te3 - Zelezny, V; Goian, V; Navrátil, Jiří; Drašar, Čestmír; Orlita, M; Piot, B. A; Prokleska, J; Misek, M; Kastil, J; Kamba, S (American Physical Society, 2021)
Infrared reflectance measurements have been carried on highly p-type Bi2Te3 crystals over the broad temperature range from 10 to 650 K and their response function investigated. An anomalous nonmonotonous temperature dependence of the plasma edge frequency is observed-with a pronounced redshift and blueshift that appear above and below room temperature, respectively. Such behavior is explained in terms of the temperature evolution of the free carrier optical weight N/m* given by particular temperature dependence of the total carrier concentration N (determined by transport measurements) and characteristic (optical) mass m*. The effective mass strongly varies from m* = 0.1m0 (m0 electron rest mass) at 10 K to m* = 0.5m0 respective m* = 0.9m0 at 650 K depending on the evaluating procedure. The interpretation is corroborated by complementary magnetotransport and magnetoreflectivity experiments.
Anomální teplotní závislost efektivní hmotnosti v p-typovém Bi2Te3
Keywords: single dirac cone; topological-insulator; electronic-structure; bismuth telluride; valence-band; carrier concentration; energy-spectrum; magneto-seebeck; point-defects; transport; topologické izolátory; Bi2Te3; efektivní hmotnost; magneto-Seebek; band structure